Notice that both A and B are multiplied by (1/2).
Thus, the given expression can be re-written as [(1/2)(A+B)]^2.
Square the (1/2) and the (A+B) separately, and then multiply together the resulting squares:
(1/4)(A^2 + 2AB + B^2)
Answer:
Step-by-step explanation:
a = -32
2. x=−3/2 ( which also equals -1.5)
Answer:
A
Step-by-step explanation:
44.99+299.49 = $344.38
$344.38 - store card ($75) = $269.48
422.76 - 269.48 - 2.5 = $150.78
Therefore answer is A
Answer:
$120
Step-by-step explanation:
Answer:
Step 1: Simplify both sides of the equation.
8−2(3−x)=4x+6
8+(−2)(3)+(−2)(−x)=4x+6(Distribute)
8+−6+2x=4x+6
(2x)+(8+−6)=4x+6(Combine Like Terms)
2x+2=4x+6
2x+2=4x+6
Step 2: Subtract 4x from both sides.
2x+2−4x=4x+6−4x
−2x+2=6
Step 3: Subtract 2 from both sides.
−2x+2−2=6−2
−2x=4
Step 4: Divide both sides by -2.
−2x
−2
=
4
−2
Step-by-step explanation: